Penerapan Model Pembelajaran Learning Cycle Untuk Meningkatkan Tanggung Jawab Mahasiswa Pgsd Fkip Universitas Bengkulu - Panut Setiono; Sri Dadi (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2021)
This study aims to improve the attitude of student responsibility in the Basic Concepts of Sociology, Anthropology, and History lectures by applying the Learning Cycle Model at PGSD FKIP UNIB. The method used is Classroom Action Research (CAR). CAR stages are planning, implementation, observation, and reflection. The results showed that the application of the Learning Cycle model in the Basic Concepts of Sociology, Anthropology, and History lectures could increase students' attitudes of responsibility. The suggestion given is that other researchers are advised to examine attitudes other than responsibility, so that the development of student attitudes can be monitored periodically.